Physico-Chemical Characterization of the Tumour Microenvironment of Pancreatic Ductal Adenocarcinoma - Calderón-Villalba, Alejandro; García-Gareta, Elena; Alamán, Pilar; Gracia, Carlos; Guerrero, Pedro E.; Mur, Carlota; Rueda, Ana; Olivera, Nerea; Sancho, Patricia; Pérez, Mª Ángeles; García-Aznar, José Manuel (Jornada de Jóvenes Investigadores del I3A, 2024)
Pancreatic ductal adenocarcinoma (PDAC) is a highly aggressive lethal malignancy that accounts for more than 90% of pancreatic cancer diagnoses. Our research is focused on the physico-chemical properties of the tumour microenvironment (TME), including its tumoural extracellular matrix (tECM) and its impact on the development of new therapies.